Modelling of Nitrate Movement and Leaching Losses Under Wetland Moisture Regime - Singh, K G; Sondhi, S K; Kumar, Mukesh (Journal of Agricultural Engineering, 2004)
The intensive agricultural production in the state of Punjab has resulted in higher NO3¯-N concentration in the ground water due to over use of agrochemicals, which leads to ground water pollution, The transport and transformation of urea, ammonium (NH4?) and nitrate (NO3) under wetland moisture profile were mathematically described as a function of depth and time, subject to either steady feed or pulse application of N. The three equations were solved simultaneously by using Laplace transformation. The analytical solution developed for transformation and movement of N03¯-N under wetland moisture regime, was used to predict the N03¯-N distribution in a soi1 column of 1.7 m deep at different time intervals. The computed distribution in a soil column with depth and time matched fairly well with the observed in the laboratory. The leaching loss under wetland moisture regime was 36.4 % of the total fertilizer (applied + available in the soil profile) and was comparable with predicted values of 31.35%.